Transitivity Analysis of Hortatory Exposition Written by Third Years Student of English Education Program at Universitas Negeri Padang. - Frisca Yolanda; M. Zaim (Journal of English Language Teaching, 2021)
The purpose of this research is to find out types of process and the most dominant process types of transitivity system, and to find out types of circumstances and the most dominant types of circumstances in Hortatory Exposition Text written by the third year student of English Education Program at Universitas Negeri Padang. The data of this research were collected through a writing test on hortatory exposition. It found 866 clauses that were obtained from 23 texts of hortatory exposition texts. The result of this research was that six types of processes occurred in the text. There were material process (59%), mental process (12%), relational process (23%), behavioral process (2%), verbal process (2%), and existential process (3%). It was found that types of material processes were the dominant process found in students' writing. Also, the result of this research found eight types of circumstances, there were Extent (6%), Location (36%), Manner (24%), Cause (26%), Accompaniment (4%), role (2%), matter (1%) and Angel (1%). The dominant types of circumstances were Location. It indicates that the characteristics of hortatory exposition text are using the material process and circumstances of Location.